Conceptual Framework of Applied Holistic Education in Physical Education and Sports: A Systematic Review of Empirical Evidence - Syaukani, Agam Akhmad; Mohd Hashim, Asha Hasnimy; Subekti, Nur (Physical Education Theory and Methodology, 2023)
Background and Study purpose. Holistic education becomes an important aspect to achieve target on education as proposed by sustainable development goals (SDGs). Many believe that education of the future should be comprehensive, aspirational and inclusive, that is holistic education. Physical education is part of school subjects that can be used to realized the educational goal of holistic learning. Through mindful planning and understanding of conceptual framework, physical activity and sports in physical education can be a powerful tool to improve the development of the whole child that includes cognitive, socio-emotional, and physical aspect. To date, there are few systematic reviews that discuss holism in the context of education, and almost none of them specifically discuss holistic education in the physical education setting. Materials and methods. This paper systematically reports previous empirical studies about the strategies used to implement holistic education in physical education class. There are 15 papers selected in this study following the Preffered Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results. As the result, this study proposes a conceptual framework for designing a teaching strategy in PE to promote whole child development. The framework encompasses the learning dimension of body, mind and spirit. All the aspects are discussed below. Conclusions. Based on the results and discussion obtained from the 15 reviewed papers, we proposed a conceptual framework to design an approach to implement holistic education in physical education.